Upregulation of proteolytic enzymes and cyclooxygenase-2 in human gingival fibroblasts stimulated with safrole - Yung-Chuan Ho; Ching-Chih Chen; Shun-Fa Yang; Fu-Mei Huang; Yu-Chao Chang (Elsevier, 2014)
Background/purpose: Areca quid chewing is associated with periodontal diseases. Many of the undesirable effects of areca quid have been attributed to safrole, a major polyphenolic compound in the inflorescence of Piper betle. Matrix metalloproteinases (MMPs, a subclass of proteolytic enzymes), plasminogen activators (PAs), and cyclooxygenase-2 (COX-2) have been reported to play an important role in the pathogenesis of periodontitis. Therefore, this study was carried out to determine the biological effects of safrole on human gingival fibroblasts (HGFs). Materials and methods: Five HGF strains were established from crown lengthening surgery. The cytotoxicity of safrole was measured by H33258 fluorescence assay and the levels of gelatinolytic and caseinolytic activities were measured by gelatin and casein zymography, respectively. Western blot analysis was used to evaluate the expression of COX-2. Results: The study results show that safrole was cytotoxic to HGFs in a concentration-dependent manner (P < 0.05). The gelatin zymograms revealed that the 72-kDa MMP-2 was secreted by HGFs. The exposure of HGFs to safrole resulted in the upregulation of MMP-2 expression (P < 0.05). Casein zymography exhibited a caseinolytic band with a molecular weight of 70 kDa, suggesting the presence of tissue-type PAs (t-PAs). The activity of t-PA was found to be upregulated by safrole (P < 0.05). In addition, safrole was also found to increase COX-2 expression in a time-dependent manner (P < 0.05). Conclusion: Overall, the results of our study show that safrole is a cytotoxic agent to HGFs. Therefore, increase in the activity of MMP-2, t-PA, and COX-2 may be involvement in the pathogenesis of areca quid-associated periodontal diseases.